A geographical database of Iberian peatland and swob recordsZenodo - Raquel Fernandes; Miguel Geraldes; Guaduneth Chico; César Capinha (Data in Brief)
Recent efforts have compiled distribution data on peatlands in the Iberian Peninsula. However, the criteria used to define these ecosystems have often been derived from regions where climates are wetter and peatlands are more widespread. As a result, in this region, many peat-accumulating wetlands were overlooked. Identifying and improving the mapping of peatland distribution is crucial for their conservation and management, as they provide important ecosystem services. Therefore, we developed an updated geographical dataset of peatlands and swobs (wetlands with the potential to form peat) of the Iberian Peninsula. Records of peatlands and swob areas in Portugal and Spain were compiled through an extensive literature review. Additionally, field surveys performed between 2011-2015, 2018-2021, and 2023-2024 provided additional records. A total of 445 records were included in our dataset, representing the up-to-date knowledge on the distribution of these ecosystems in the Iberian Peninsula. The dataset allows the identification of occurrence hotspots, highlights underrepresented regions, and provides a baseline for future research and conservation planning.